Learners’ Satisfaction on CALL - Munsakorn, Nuttanuch (Mediterranean Journal of Social Sciences, 2012)
The study investigated the students’ satisfaction on CALL as classified by their gender, and computer literacy. Aquestionnaire is used for collecting data. Proportional stratified random sampling was employed to formulate a sample of 400 BUstudents. These students answered through the questionnaire which asked about their satisfaction on CALL in a form of Likert’sfive-rating scale. The data were statistically analyzed in terms of mean and standard deviation, t-test, One-Way Analysis ofVariance. The results of this study showed that the overall student’s satisfaction of Bangkok University was at very high level,and significant differences existed in student’s satisfaction on CALL of two independent variables: gender and computer literacy.The findings of this research would help the instructors to improve the process and material for language teaching with CALL.